Variations in Magnetic Resonance Imaging Provision and Processes among Canadian Academic Centres. Issue 1 (February 2017) - Vanderby, Sonia; Badea, Andreea; Peña Sánchez, Juan Nicolás; Kalra, Neil; Babyn, Paul
Purpose: Increasing demand has led to questions regarding the appropriateness of advanced imaging exams, particularly for magnetic resonance imaging (MRI). The study aimed to explore variability in MRI service provision and request variation within Canadian academic medical imaging departments, particularly factors potentially affecting appropriate MRI service provision. Methods: All Canadian academic centres with medical imaging residency programs were invited to participate. Participation involved completing an institution-level survey and submitting exam requests for all MRI exams completed in a common 24-hour period. The surveys and request forms were analysed and contrasted. Results: The 13 participating institutions reported scanner operating hours per week ranging from 101-672; large urban centres typically had higher hours. A total of 42% of sites housed multiple scanners, and 28% housed a 3-T scanner. Most accept requests from all general practitioners and specialists. Only 1 institution has a solely electronic request submission process. Requisitions are focused on patient safety, including contrast considerations, metallic foreign bodies, and implants. Request prioritization scales vary substantially across institutions. Few use referral guidelines to evaluate request appropriateness. Conclusions: Our analysis showed great variation among facility-level factors such as hours of operation, request forms, and prioritization scales among institutions and facilities. Opportunities exist to create standardized processes and improve request forms to focus more on specific information required for appropriateness, increase consistency in patient care, and promote demand balancing, minimizing unnecessary exams and therefore reducing wait times.